The effect of Two Stay Two Stray learning model assisted by wordwall application on student learning outcomes - Reinita, Reinita; Rusdyani, Devi (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2024)
This study employs a quantitative approach, utilizing a quasi-experimental design known as a non-equivalent control group design. The research instruments consist of validated test items in the form of multiple-choice questions. These instruments undergo preliminary trials and subsequent analysis, including assessments of validity, reliability, differentiating power, and difficulty, ensuring the production of valid and reliable research tools. Twenty-six validated questions were utilized, demonstrating a high reliability coefficient of 0.8973, meeting stringent reliability criteria and indicating the trustworthiness of the test questions. Data analysis was conducted using a t-test, with a significance level set at 5% (0.05). Post-test results revealed a higher average score in the experimental group (80.22) compared to the control group (71.00). The t-test analysis yielded a t-count of 2.8089, exceeding the critical t-value of 2.0106. Additionally, the N-gain scores showed a significant average increase in the experimental group (31.49%) compared to the control group (24.35%). The study findings indicate a noteworthy disparity in learning outcomes between the two groups subjected to different treatments. Specifically, learning outcomes in the experimental group surpassed those in the control group following the intervention. Thus, it can be inferred that the implementation of the Two Stay Two Stray cooperative model, supported by the Wordwall application, positively impacts student learning outcomes.